Towards sustainable and intensive forest management in Northwest Russia - Korotkov, Vladimir; Leinonen, Timo; Palenova, Maria; Filipchuk, Andrey; Nesterenko, Yury (Finnish Forest Research Institute, 2008)
Northwest Russia is the most important forest industry district producing 34% of the merchantable wood, 32% of the sawn wood, and 64% of the paper in Russia in 2007. The combination of the rich and diverse forest resources, rather developed forest infrastructure, long forest industy history, and geographical location close to Western markets and the major domestic markets of St. Petersburg and Moscow increase its attractiveness both from the economic and ecological point of view. The purpose was therefore to overview the development of forest management and to describe the main tendencies of forest use, regeneration, and nature conservation for Russia in general and the Northwest in particular towards an intensive model of forest management for this area, which would cover the period from just after the collapse of the Soviet Union up to the passage of the new Forest Code in 2007.In the Northwest, forest use has been rather extensive during the period 1993 2006, on average, about 40% of the allowable annual cut, which applies solely to final felling, was utlized. The actual volume of intermediate felling has been insignificant in comparison to what is needed to increase the quality of stands; in 2005 and 2006, it comprised about a tenth of the area and a third of the volume. In the area, during the period 1999 2006, almost every fifth hectare of clear felling was left without active forest regeneration measures. This development threatens the sustainability of forest management by reducing the quality of newly forming stands. The age-class structure is skewed due to this and other past forest management. More than half of the total area of coniferous forests is still composed of mature and overmature stands. These types of coniferous stands prevail in the Komi republic, and the Arkhangelsk and Murmansk regions, this is because of the economically limited accessibility and the significantly low productivity of these forest resources.Although the forests of Northwest Russia are of great economic importance, the ...